2013
DOI: 10.1634/theoncologist.2012-0322
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor as a Novel Target for Treatment of Breast Cancer

Abstract: CME Learning Objectives Explain the process by which tissue factor (TF) initiates blood coagulation and is implicated in tumor progression. Describe the proposed mechanisms of targeting TF in malignancy. Discuss the applications of TF targets in developing new treatments for aggressive cancers including triple‐negative breast cancer. Tissue factor (TF), a 47‐kDa transmembrane glycoprotein that initiates blood coagulation when complexed with factor VIIa (FVIIa), is expressed in several tumor types. TF has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…Tissue factor (TF), a membrane-associated glycoprotein, has emerged as the central player in the relationship between the hemostatic system and cancer progression (13,14,(22)(23)(24)(25)(26). TF binds and activates coagulation factor FVII, which in turn triggers the downstream coagulation cascade leading to thrombin generation and clot formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue factor (TF), a membrane-associated glycoprotein, has emerged as the central player in the relationship between the hemostatic system and cancer progression (13,14,(22)(23)(24)(25)(26). TF binds and activates coagulation factor FVII, which in turn triggers the downstream coagulation cascade leading to thrombin generation and clot formation.…”
Section: Introductionmentioning
confidence: 99%
“…Early screening studies have identified TF as a differentially expressed gene in invasive cell lines such as MDA-MB-231 breast cancer cell line. Enhanced TF expression has also been found in a variety of solid tumors including breast cancers, in which it associates with decreased overall survival or shorter recurrence-free survival (26). TF is a downstream target of several oncogenic pathways (RAS, HER2, MET, SHH), of the loss of tumor suppressors such as PTEN or p53, and of transcriptional regulation by NFkB, AP-1, or Egr-1 transcription factors (24,25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of the TF concentration in the plasma of the subjects, expressed per mg of protein, with the TF concentration in tumor tissue homogenates presented that, in the case of meningiomas, the TF concentration was 157-fold higher in tumor tissue homogenate than in the plasma The examination of the TF concentration in the blood of patients with various types of cancer (breast cancer, pancreatic cancer, colon cancer) demonstrates a high TF concentration, which was seen as the presence of thrombotic risk or even overt thrombosis. 10 Also, patients with gliomas demonstrated high TF levels, which significantly correlated with the degree of malignancy. 11 The histochemical and immunological tests of the tissue fragments derived from gliomas indicated a TF expression in tumor cells and in endothelium in new vessels created in the process of angiogenesis.…”
Section: Resultsmentioning
confidence: 97%
“…TF has become one of the targets of targeted therapy for breast cancer cells (Cole et al, 2013), and is considered an important aspect of breast cancer research (Santos et al, 2013). Studies have shown that TF and MMP -9 expression is significantly correlated with breast cancer cells in humans and dogs (Zhao et al, 2008;Hu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%